Comparison of mRNA gene expression by RT-PCR and DNA microarray - Wiguins Etienne; Martha H. Meyer; Johnny Peppers; Ralph A. Meyer (BioTechniques, 2004)
Few studies have compared the quantification of mRNA by DNA microarray to the results obtained by reverse transcription PCR (RT-PCR). In this study, mRNA was collected from the healing femoral fracture callus of adult and juvenile rats at various times after fracture. Ten samples were measured by both methods for 26 genes. For RT-PCR, mRNA was reverse transcribed, amplified, electrophoresed, blotted, and probed with 32P-labeled internal oligonucleotides, which were quantified. For DNA microarray, the mRNA was processed to biotin-labeled cRNA, hybridized to 10 Affymetrix® Rat U34A microarrays, and quantified. Correlation coefficients (r) for each gene for the agreement between RT-PCR and microarray ranged from −0.48 to +0.93. This variation made the interpretation gene-specific. Genes with moderate expression levels gave the highest r values. Increased numbers of absent calls by the microarray software and increased separation between the location of the PCR primers and the microarray probes both led to reduced agreement. Microarray analysis suggested a floor effect in expression levels measured by RT-PCR for two genes. In conclusion, moderate mRNA expression levels with overlap in the location of PCR primers and microarray probes can yield good agreement between these two methods.